A legal analysis of the application of articles I and III of the GATT 1994 on the economic development of ECOWAS member states - Ogbonna, Joseph Ifeanyichukwu (Brunel University, 2012)
This dissertation examines the tension inherent in the relationship between the Economic Community of West African States (ECOWAS) as Member States Parties of the GATT/WTO and the GATT/WTO regime. It focuses specifically on the tension triggered off by the requirements of Article I – the Most-Favoured-Nation principle (MFN) and Article III – the National Treatment principle (NT) GATT 1994. It shows that while the non-discrimination principles are meant to promote trade liberalisation and economic growth, they produce the opposite effect in developing and least developed countries like ECOWAS and aggravate the tension between those countries and the WTO. It argues that the MFN is used to deny market access to the developing countries by exposing them to stiff but unequal competitive conditions and the NT to deny national governments the policy space to protect and promote national industries, employment and economic growth. It challenges the general assumption that the MFN and the NT are good and in the interest of all the WTO Members and rather identifies them as lynch-pins of economic development in the ECOWAS region. It also shows, contrary to the assumption of non-participation, how the ECOWAS High Contracting Parties are adapting their trading systems and harmonising their laws to the key provisions of Articles I and III of the GATT. It shows that the principles of non-discrimination are the outcome of the standard-setting procedures legally formulated as the SPS and TBT Agreements which favour the developed countries and how the Dispute Settlement Body has rejected the ‘aims-and-effect’ approach, taken a literal approach, overly emphasising trade liberalisation to the neglect of market access and economic development. This dissertation concludes that it is pre-mature for ECOWAS to assume Articles I and III obligations and recommends using the provisions of Article XXIV to build up effective influence through regional organisations and incrementally uniting to transform the GATT.This study is funded by the Brunel Law School
Keywords: ECOWAS; GATT; Tension; WTO; World Trade Organisation

Trade agreements and bilateral trade in sub-Saharan Africa: Estimating the trade effects of the EU-ACP PTA and RTAs - Turkson, Festus Ebo (CREDIT Research Paper, 2012)
This paper on Trade Agreements within SSA, is an assessment of the ex post bilateral trade effect of the European Union-African Caribbean Pacific Preferential Trade Agreement (EU-ACP PTA) and sub-regional regional trade agreements (RTAs) on bilateral trade involving SSA countries. The main objective is to find out if EU trade preferences and regional trade agreements within SSA had increased trade flows. Estimating a gravity model augmented with measures of trade agreements, the paper made use of bilateral trade flows and key gravity covariates from CEPII database on 73 countries (48 SSA and 25 EU countries) over the period 1960-2006. After controlling for the endogeneity of the trade agreement dummy, accounting for multilateral price resistance and zero-valued trade flows, the findings indicate that the EU-ACP PTA and RTAs within ECOWAS and SADC have a positive and significant impact on bilateral trade involving SSA countries. In some cases the relative impact of the sub-regional RTAs was found to be stronger than the EU-ACP non-reciprocal PTA. The results therefore indicate the need for developing countries especially within SSA to focus on expanding and integrating regional markets in order to significantly improve trade performance.
Keywords: Bilateral Exports; Developing countries; Domestic Trade; Gravity Model; International Trade; Sub-Saharan Africa; Trade Costs

Using observable trade data to measure bilateral trade costs in sub-Saharan Africa - Turkson, Festus Ebo (CREDIT Research Paper, 2012)
Following closely the analytical approach adopted by Head and Mayer (2004) and Novy (2010), this paper derives a micro-founded bilateral trade cost measure for sub-Saharan Africa (SSA) as a function of observable domestic and inter-national trade data. The derived measure of trade cost by Novy (2010), consistent with the Ricardian and heterogeneous firm's models of trade, enables us to track changes in trade costs in SSA over time. This is a significant contribution to the trade cost literature in SSA because measures of many components of trade frictions in SSA have been unreliable. Based on bilateral trade data from BACI and production figures from the Trade, Production and Protection database by Nicita and Olarreaga (2007) for the period 1980-2003, our estimates of the tariff equivalent bilateral trade costs measure indicate that on average trade costs in SSA are relatively higher than other regions, confirming evidence which indicates trading costs in SSA to be the highest within the global trading system. The estimates indicate that SSA countries traded with each other at a lower cost than they did with other regions with the exception of the EU. Within SSA, member countries of economic blocs traded at relatively lower costs than trade with non-member countries. Using each of the main five economic blocs within SSA as a reference, overall average relative bilateral trade costs within bloc was significantly lower than across blocs. This paper therefore argues for increased efforts at regional integration within SSA to derive benefits from lower trade costs.
Keywords: Bilateral Exports; Gravity Model; Sub-Saharan Africa; Trade Costs